Composite fiber and process for producing the same

CN122484960BActive Publication Date: 2026-10-30HEBEI XINSHIJIYE SPRAY APPLIED THERMAL & ACOUSTIC INSULATION
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610975381.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-07-02
Publication Date
2026-10-30
Estimated Expiration
2046-07-02

AI Technical Summary

Technical Problem

[0005]本发明提出一种复合纤维及其制备工艺,解决了相关技术中复合纤维在沥青混凝土基体中难以实现单丝级均匀分布进而导致沥青混凝土动稳定度不足的问题

Benefits of technology

本发明复合纤维的原料中,在聚合物纤维中添加矿粉,矿粉颗粒细小且表面具有一定的粗糙性与吸附性,当混入由聚丙烯腈纤维、聚丙烯纤维和聚酯纤维组成的聚合物纤维中时,矿粉可均匀分布在各聚合物纤维之间,降低纤维之间的接触面积与粘结力,使原本成束的聚合物纤维在拌合过程中更易被分散成单丝状态,有效打破聚合物纤维因分子间作用力或静电吸引而产生的团聚现象,良好的分散性让聚合物纤维能更均匀地融入改性玄武岩纤维和木质纤维体系中,进而在沥青混凝土内部形成分布更均匀、结构更完整的纤维网络,进而提升沥青混凝土的动稳定度。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The application relates to the technical field of composite materials, and discloses a composite fiber and a preparation process thereof.The composite fiber is composed of the following raw materials in percentage by weight: 3-15% of polymer fiber, 3-15% of wood fiber, and the balance of modified basalt fiber; the polymer fiber is composed of the following raw materials in percentage by weight: 60-80% of polyacrylonitrile fiber, 5-10% of polypropylene fiber, 1-5% of mineral powder, and the balance of polyester fiber.Through the technical scheme, the problem that the composite fiber in the related art is difficult to realize uniform distribution in a single filament level in an asphalt concrete matrix and further leads to insufficient dynamic stability of the asphalt concrete is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of composite materials technology, specifically to a composite fiber and its preparation process. Background Technology

[0002] In the field of road engineering, road concrete, as a core material, must simultaneously meet multiple requirements such as high strength, crack resistance, fatigue resistance, and durability. Although traditional concrete has high compressive strength, it is brittle and has low tensile strength, making it susceptible to cracking due to vehicle loads, temperature stress, and environmental erosion, leading to deterioration of structural performance.

[0003] The introduction of composite fibers offers a new approach to solving this problem. Compared to single fibers, composite fibers can optimize concrete performance through synergistic effects of multiple properties and perspectives. For example, in patent document CN 119349916 A, inorganic and organic fibers are added simultaneously as raw materials to prepare composite fibers. However, in this application, the dynamic stability of asphalt concrete only reaches 8000 cycles / mm. -1 This indicator is still insufficient for engineering needs in heavy traffic or high-temperature areas. There are two main reasons for this phenomenon. First, inorganic fibers are prone to agglomeration due to their strong surface polarity, while organic fibers are difficult to disperse due to their surface inertness. Existing mechanical mixing or simple surface treatment is not enough to achieve a uniform distribution of various fibers at the monofilament level in the asphalt matrix. Local fiber agglomeration areas will form stress concentration points, which will aggravate plastic flow at high temperatures and limit further improvement of dynamic stability.

[0004] Therefore, it is essential to develop a composite fiber that can achieve uniform distribution at the monofilament level in asphalt concrete matrix and has a low cost, and apply it to road concrete to improve the dynamic stability of road concrete. Summary of the Invention

[0005] This invention proposes a composite fiber and its preparation process, which solves the problem in related technologies that it is difficult to achieve uniform distribution of composite fibers at the monofilament level in asphalt concrete matrix, thus leading to insufficient dynamic stability of asphalt concrete.

[0006] The technical solution of the present invention is as follows: The present invention proposes a composite fiber, which is composed of the following raw materials by weight percentage: 3%~15% polymer fiber, 3%~15% wood fiber, and the balance being modified basalt fiber; the polymer fiber is composed of the following raw materials by weight percentage: 60%~80% polyacrylonitrile fiber, 5%~10% polypropylene fiber, 1%~5% mineral powder, and the balance being polyester fiber.

[0007] As a further technical solution, the mineral powder includes two or more of the following: calcium carbonate powder, barite powder, mullite powder, wollastonite powder, mica powder, and talc powder. The particle size of the mineral powder is 300-1000 mesh, for example, it can be 300 mesh, 400 mesh, 500 mesh, 600 mesh, 700 mesh, 800 mesh, 900 mesh, or 1000 mesh, preferably 500 mesh.

[0008] As a further technical solution, the mineral powder is composed of barite powder and talc powder in a mass ratio of 1:1.

[0009] In the raw materials of the composite fiber of the present invention, mineral powder is added to the polymer fiber, which can synergistically improve the dispersibility of the composite fiber, improve the mechanical properties of the composite fiber in asphalt concrete, improve the high temperature resistance of asphalt concrete, and thus improve the dynamic stability of asphalt concrete.

[0010] As a further technical solution, the preparation method of the polymer fiber includes the following steps: mixing the raw materials of the polymer fiber, opening and dissociating them into monofilament polymer fibers, spraying paraffin oil after opening, and obtaining the polymer fiber, wherein the amount of paraffin oil sprayed is 0.1% to 1% of the mass of the polymer fiber.

[0011] As a further technical solution, the paraffin oil has a density (20℃) of 845.3 kg / m³, standard: SH / T0604; a kinematic viscosity (40℃) of 20.5 mm / s, standard: GB / T 220; an open flash point >200℃, standard: GB / T 3536; and a pour point -40℃, standard: GB / T 3535.

[0012] As a further technical solution, the polymer fiber is a monofilamentous polymer fiber with a diameter of 10~30μm and a length of 3~12mm; the wood fiber is a flocculent wood fiber with a length of 2~3mm.

[0013] As a further technical solution, the wood fiber is a flocculent wood fiber with a service temperature of <210℃, standard: JT / T533; ash content of <10.0%, standard: GB / T22877; and a length of 2~3mm, standard: JT / T533.

[0014] In the raw materials of the composite fiber of the present invention, the polymer fiber is a monofilament polymer fiber. After being dispersed by a high-speed opener, the fiber bundle is dispersed and fluffy into a monofilament, which improves the dispersion efficiency. After dispersion, paraffin oil is sprayed on to form a physical isolation layer on the fiber surface, which prevents the dissociated monofilament fibers from re-aggregating due to excessive surface energy. It can also play a dust suppression role during the processing.

[0015] As a further technical solution, the high-speed opening speed is 2000~5000rpm, for example, it can be 2000rpm, 2500rpm, 3000rpm, 3500rpm, 4000rpm, 4500rpm, or 5000rpm, preferably 4000rpm, and the high-speed opening time is 2~5s, for example, it can be 2s, 3s, 4s, or 5s, preferably 3s.

[0016] As a further technical solution, the modified basalt fiber is obtained by spraying a modifier onto basalt fiber, and the mass ratio of the modifier to the basalt fiber in the raw material of the modified basalt fiber is 0.2~3:100.

[0017] As a further technical solution, the silane coupling agent includes one or more of epoxy silane coupling agents, sulfurized silane coupling agents, vinyl silane coupling agents, and acyloxy silane coupling agents, preferably sulfurized silane coupling agents.

[0018] As a further technical solution, the sulfurized silane coupling agent is sulfurized silane coupling agent Z-6940.

[0019] As a further technical solution, the modifier also includes polymethyl methacrylate, and when the modifier is composed of a silane coupling agent and polymethyl methacrylate, the mass ratio of the silane coupling agent to the polymethyl methacrylate is 2:1~2.

[0020] As a further technical solution, the polymethyl methacrylate is composed of polymethyl methacrylate Altuglas BS 203 and polymethyl methacrylate Altuglas BS 215 in a mass ratio of 2:2~3.

[0021] In the raw materials of the composite fiber of this invention, the modifier of the modified basalt fiber is composed of a silane coupling agent and polymethyl methacrylate (PMMA). The PMMA is composed of PMMA Altuglas BS 203 and PMMA Altuglas BS 215. PMMA Altuglas BS 203 has moderate fluidity and can better wet and blend with asphalt. PMMA Altuglas BS 215 has higher molecular weight and mechanical strength. When the two are combined in a specific ratio, they can form a network structure with a balance of rigidity and toughness in the asphalt system, thereby enhancing the Marshall modulus of asphalt concrete.

[0022] This invention also proposes a process for preparing a composite fiber, comprising the following steps: S1. Modified basalt fiber is obtained by spraying a modifier onto the surface of the basalt fiber. After the modified basalt fiber is desiccated, granulated, slag removed by sieving, shortened and opened, paraffin oil is sprayed onto the surface of the modified basalt fiber to prepare modified flocculent basalt fiber. S2. Spray paraffin oil onto the surface of the wood fiber, add the modified flocculent basalt fiber and the polymer fiber, mix evenly to obtain the material; S3. After the material is combed twice, it is then air-separated for slag removal and compressed for packaging to obtain composite fiber.

[0023] In the preparation process of the composite fiber of the present invention, in step S1, paraffin oil is coated on the surface of the modified basalt fiber, which can not only suppress construction dust, but also enhance the compatibility of the fiber with asphalt concrete.

[0024] As a further technical solution, in step S1, the amount of paraffin oil sprayed is 0.5% to 2% of the mass of the modified basalt fiber.

[0025] As a further technical solution, in step S2, the amount of paraffin oil sprayed is 0.1% to 1% of the mass of the wood fiber.

[0026] As a further technical solution, in step S2, the mixing speed is 10~60 rpm, for example, it can be 10 rpm, 20 rpm, 30 rpm, 40 rpm, 50 rpm, or 60 rpm, preferably 30 rpm.

[0027] As a further technical solution, the two combing processes have different combing speeds. During the first combing process, the receiving roller speed of the first combing machine is 30-60 rpm, for example, 30 rpm, 40 rpm, 50 rpm, or 60 rpm, preferably 50 rpm. The combing roller speed is 800-1200 rpm, for example, 800 rpm, 900 rpm, 1000 rpm, 1100 rpm, or 1200 rpm, preferably 1000 rpm. The distance between the two rollers is 3mm-7mm, for example, 3mm, 4mm, 5mm, or 6mm. The diameter of the two rollers is 7mm, preferably 5mm; during the second carding process, the receiving roller speed of the second carding machine is 30~60rpm, for example, 30rpm, 40rpm, 50rpm, 60rpm, 70rpm, preferably 60rpm, the carding roller speed is 1200~1500rpm, for example, 1200rpm, 1300rpm, 1400rpm, 1500rpm, preferably 1400rpm, and the distance between the two rollers is 1mm~5mm, for example, 1mm, 2mm, 3mm, 4mm, 5mm, preferably 3mm.

[0028] As a further technical solution, after air classification and slag removal, the content of slag balls with a particle size >150μm is <20wt%.

[0029] As a further technical solution, the macroscopic state of the composite fiber is flocculent, uniform, soft, and fluffy, with an oil absorption rate of 4 to 9 times.

[0030] As a further technical solution, the amount of composite fiber added to the asphalt mixture is 0.3% to 1.5% of the mass of the asphalt mixture.

[0031] As a further technical solution, the composite fibers are fed in a pneumatic manner during use to achieve uniform distribution of the composite fibers in the asphalt mixture.

[0032] The working principle and beneficial effects of this invention are as follows: In the raw materials of the composite fiber of this invention, mineral powder is added to the polymer fiber. The mineral powder particles are fine and have a certain degree of surface roughness and adsorption. When mixed into the polymer fiber composed of polyacrylonitrile fiber, polypropylene fiber and polyester fiber, the mineral powder can be evenly distributed between the polymer fibers, reducing the contact area and adhesion between the fibers. This makes it easier for the originally bundled polymer fibers to be dispersed into monofilaments during the mixing process, effectively breaking the agglomeration phenomenon of polymer fibers caused by intermolecular forces or electrostatic attraction. The good dispersibility allows the polymer fibers to be more evenly integrated into the modified basalt fiber and wood fiber system, thereby forming a more evenly distributed and structurally complete fiber network inside the asphalt concrete, thus improving the dynamic stability of the asphalt concrete. Detailed Implementation

[0033] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0034] In the following text: Mineral powder: The mineral powder is composed of barite powder and talc powder in a mass ratio of 1:1; Barite powder: average particle size is 500 mesh; Talc powder: average particle size is 500 mesh; Wood fibers: fluffy, 3 mm in length; Polyacrylonitrile fibers: bundled, 20 μm in diameter and 3 mm in length; Polypropylene fibers: bundled, 20μm in diameter and 3mm in length; Polyester fiber: in bundles, with a diameter of 20μm and a length of 3mm.

[0035] Example 1 The composite fiber is composed of the following raw materials by weight percentage: 3% polymer fiber, 3% wood fiber, and the balance being modified basalt fiber; The polymer fiber is composed of the following raw materials by weight percentage: 60% polyacrylonitrile fiber, 5% polypropylene fiber, 1% mineral powder, and the balance being polyester fiber. The preparation method of polymer fiber includes the following steps: mixing the raw materials of polymer fiber, loosening at 4000 rpm for 3 seconds to dissociate into monofilament polymer fiber, and spraying paraffin oil (the amount of spraying is 0.1% of the mass of polymer fiber) after loosening to obtain polymer fiber; A process for preparing composite fibers includes the following steps: S1. Modified basalt fiber is obtained by spraying a modifier (the mass ratio of modifier to basalt fiber is 0.2:100) onto the surface of basalt fiber. After desiccation, granulation, slag removal by sieving, shortening and opening, paraffin oil (0.5% of the mass of modified basalt fiber) is sprayed onto the surface of the modified basalt fiber to prepare modified flocculent basalt fiber. The modifier is silane coupling agent Z-6940. S2. Spray paraffin oil onto the surface of wood fibers (the amount of spraying is 0.1% of the mass of wood fibers), add modified flocculent basalt fibers and polymer fibers, mix evenly at 30 rpm to obtain the material; S3. After the material is combed twice, it is then air-separated for slag removal and compressed for packaging to obtain composite fiber. In the first combing process, the receiving roller speed of the first combing machine is 50 rpm, the combing roller speed is 1000 rpm, and the distance between the two rollers is 5 mm. In the second combing process, the receiving roller speed of the second combing machine is 60 rpm, the combing roller speed is 1400 rpm, and the distance between the two rollers is 3 mm.

[0036] Example 2 The composite fiber is composed of the following raw materials by weight percentage: 7% polymer fiber, 7% wood fiber, and the balance being modified basalt fiber; The polymer fiber is composed of the following raw materials by weight percentage: 70% polyacrylonitrile fiber, 8% polypropylene fiber, 3% mineral powder, and the balance being polyester fiber. The preparation method of polymer fiber includes the following steps: mixing the raw materials of polymer fiber, loosening at 4000 rpm for 3 seconds to dissociate into monofilament polymer fiber, and spraying paraffin oil (the amount of spraying is 0.5% of the mass of polymer fiber) after loosening to obtain polymer fiber; A process for preparing composite fibers includes the following steps: S1. Modified basalt fiber is obtained by spraying a modifier (the mass ratio of modifier to basalt fiber is 1.5:100) onto the surface of basalt fiber. After desiccation, granulation, slag removal by sieving, shortening and opening, paraffin oil (1.2% of the mass of modified basalt fiber) is sprayed onto the surface of the modified basalt fiber to prepare modified flocculent basalt fiber. The modifier is silane coupling agent Z-6940. S2. Spray paraffin oil onto the surface of wood fibers (spraying amount is 0.5% of the mass of wood fibers), add modified flocculent basalt fibers and polymer fibers, mix evenly at 30 rpm to obtain the material; S3. After the material is combed twice, it is then air-separated for slag removal and compressed for packaging to obtain composite fiber. In the first combing process, the receiving roller speed of the first combing machine is 50 rpm, the combing roller speed is 1000 rpm, and the distance between the two rollers is 5 mm. In the second combing process, the receiving roller speed of the second combing machine is 60 rpm, the combing roller speed is 1400 rpm, and the distance between the two rollers is 3 mm.

[0037] Example 3 The composite fiber is composed of the following raw materials by weight percentage: 15% polymer fiber, 15% wood fiber, and the balance being modified basalt fiber; The polymer fiber is composed of the following raw materials by weight percentage: 80% polyacrylonitrile fiber, 10% polypropylene fiber, 5% mineral powder, and the balance being polyester fiber. The preparation method of polymer fiber includes the following steps: mixing the raw materials of polymer fiber, loosening at 4000 rpm for 3 seconds to dissociate into monofilament polymer fiber, and spraying paraffin oil (the amount of spraying is 1% of the mass of polymer fiber) after loosening to obtain polymer fiber. A process for preparing composite fibers includes the following steps: S1. Modified basalt fiber is obtained by spraying a modifier (the mass ratio of modifier to basalt fiber is 3:100) onto the surface of basalt fiber. After desiccation, granulation, slag removal by sieving, shortening and opening, paraffin oil (2% of the mass of modified basalt fiber) is sprayed onto the surface of the modified basalt fiber to prepare modified flocculent basalt fiber. The modifier is silane coupling agent Z-6940. S2. Spray paraffin oil onto the surface of wood fibers (1% of the mass of wood fibers), add modified flocculent basalt fibers and polymer fibers, mix evenly at 30 rpm to obtain the material; S3. After the material is combed twice, it is then air-separated for slag removal and compressed for packaging to obtain composite fiber. In the first combing process, the receiving roller speed of the first combing machine is 50 rpm, the combing roller speed is 1000 rpm, and the distance between the two rollers is 5 mm. In the second combing process, the receiving roller speed of the second combing machine is 60 rpm, the combing roller speed is 1400 rpm, and the distance between the two rollers is 3 mm.

[0038] Example 4 Compared with Example 2, Example 4 differs in that barite powder (average particle size of 500 mesh) and talc powder (average particle size of 500 mesh) are replaced with barite powder (average particle size of 100 mesh) and talc powder (average particle size of 100 mesh).

[0039] Example 5 Compared with Example 2, Example 5 differs in that barite powder (average particle size of 500 mesh) and talc powder (average particle size of 500 mesh) are replaced with barite powder (average particle size of 1500 mesh) and talc powder (average particle size of 1500 mesh).

[0040] Example 6 The composite fiber is composed of the following raw materials by weight percentage: 7% polymer fiber, 7% wood fiber, and the balance being modified basalt fiber; The polymer fiber is composed of the following raw materials by weight percentage: 70% polyacrylonitrile fiber, 8% polypropylene fiber, 3% mineral powder, and the balance being polyester fiber. The preparation method of polymer fiber includes the following steps: mixing the raw materials of polymer fiber, spraying paraffin oil (the amount of spraying is 0.5% of the mass of polymer fiber) to obtain polymer fiber; A process for preparing composite fibers includes the following steps: S1. Modified basalt fiber is obtained by spraying a modifier (the mass ratio of modifier to basalt fiber is 1.5:100) onto the surface of basalt fiber. After desiccation, granulation, slag removal by sieving, shortening and opening, paraffin oil (0.5% of the mass of modified basalt fiber) is sprayed onto the surface of the modified basalt fiber to prepare modified flocculent basalt fiber. The modifier is silane coupling agent Z-6940. S2. Spray paraffin oil onto the surface of wood fibers (spraying amount is 0.5% of the mass of wood fibers), add modified flocculent basalt fibers and polymer fibers, mix evenly at 30 rpm to obtain the material; S3. After the material is combed twice, it is then air-separated for slag removal and compressed for packaging to obtain composite fiber. In the first combing process, the receiving roller speed of the first combing machine is 50 rpm, the combing roller speed is 1000 rpm, and the distance between the two rollers is 5 mm. In the second combing process, the receiving roller speed of the second combing machine is 60 rpm, the combing roller speed is 1400 rpm, and the distance between the two rollers is 3 mm.

[0041] Example 7 The difference between Example 7 and Example 2 is that the modifier for the modified basalt fiber consists of sulfurized silane coupling agent Z-6940 and polymethyl methacrylate Altuglas BS 203 in a mass ratio of 2:1.

[0042] Example 8 The difference between Example 8 and Example 2 is that the modifier for the modified basalt fiber consists of a sulfurized silane coupling agent Z-6940 and polymethyl methacrylate Altuglas BS 203 in a mass ratio of 1:1.

[0043] Example 9 The difference between Example 9 and Example 8 is that the polymethyl methacrylate Altuglas BS 203 is replaced with an equal amount of polymethyl methacrylate Altuglas BS 203 and polymethyl methacrylate Altuglas BS 215 in a mass ratio of 1:1.

[0044] Example 10 The difference between Example 10 and Example 8 is that the polymethyl methacrylate Altuglas BS203 was replaced with an equal amount of polymethyl methacrylate Altuglas BS 203 and polymethyl methacrylate Altuglas BS 215 in a mass ratio of 2:3.

[0045] Comparative Example 1 Compared with Example 2, Comparative Example 1 differs in that the polymer fiber is composed of the following raw materials by weight percentage: 70% polyacrylonitrile fiber, 8% polypropylene fiber, and the remainder is polyester fiber.

[0046] The prepared composite fiber was added to asphalt concrete at a concentration of 0.4%. The asphalt concrete consisted of SBS-modified asphalt and a base material with an asphalt-aggregate ratio of 5.7. The base material gradation was 0-3mm, 3-6mm, 6-11mm, and 11-16mm, with a mass ratio of 0.12:0.10:0.27:0.41 for each grade. The base material was composed of 10-15mm and 5-10mm and 3-5mm and 0-3mm manufactured sand, respectively, and was obtained after sieving according to particle size. In addition, the base material also included mineral powder, with a mass ratio of each grade of base material to mineral powder of 0.12:0.10:0.27:0.41:0.10.

[0047] Experimental Example 1 The asphalt concrete with composite fibers prepared in Examples 1-6 and Comparative Example 1 were tested for dynamic stability according to the test methods in T0719-2011, as specified in JTG E42-2005 "Test Procedures for Asphalt and Asphalt Concrete in Highway Engineering".

[0048] The test results are shown in Table 1: Table 1. Performance test results of composite fibers prepared in Examples 1-6 and Comparative Example 1 in asphalt concrete.

[0049] As shown in Table 1, when the raw materials of polymer fibers contain mineral powder with a particle size of 300-1000 mesh, the polymer fibers, after being opened and then combined with wood fibers and modified basalt fibers, can improve the dynamic stability of asphalt concrete.

[0050] Experiment Example 2 The asphalt concrete with the composite fibers prepared in Examples 2 and 7-10 were respectively added, and the Marshall modulus of the asphalt concrete was tested according to the test method in T 0709-2011, as specified in JTG E42-2005 "Test Procedures for Asphalt and Asphalt Concrete in Highway Engineering".

[0051] The test results are shown in Table 2: Table 2. Performance test results of the composite fibers prepared in Examples 2 and 7-10 in asphalt concrete.

[0052] As shown in Table 2, when the modifier of modified basalt fiber is composed of silane coupling agent and polymethyl methacrylate, and when the polymethyl methacrylate is composed of polymethyl methacrylate Altuglas BS 203 and polymethyl methacrylate Altuglas BS 215, the Marshall modulus of asphalt concrete can be further improved.

[0053] The above are merely preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A composite fiber, characterized in that, It is composed of the following raw materials by weight percentage: 3%~15% polymer fiber, 3%~15% wood fiber, and the balance being modified basalt fiber; the polymer fiber is composed of the following raw materials by weight percentage: 60%~80% polyacrylonitrile fiber, 5%~10% polypropylene fiber, 1%~5% mineral powder, and the balance being polyester fiber. The mineral powder includes two or more of the following: calcium carbonate powder, barite powder, mullite powder, wollastonite powder, mica powder, and talc powder, and the particle size of the mineral powder is 300-1000 mesh. The modified basalt fiber is obtained by spraying a modifier onto basalt fiber. In the raw materials of the modified basalt fiber, the mass ratio of the modifier to the basalt fiber is 0.2~3:

100. The modifier includes a silane coupling agent, which includes one or more of epoxy silane coupling agents, sulfurized silane coupling agents, vinyl silane coupling agents, and acyloxy silane coupling agents. The modifier also includes polymethyl methacrylate, and when the modifier is composed of a silane coupling agent and polymethyl methacrylate, the mass ratio of the silane coupling agent to the polymethyl methacrylate is 2:1~2.

2. The composite fiber according to claim 1, characterized in that, The preparation method of the polymer fiber includes the following steps: mixing the raw materials of the polymer fiber, opening and dissociating them into monofilament polymer fibers, spraying paraffin oil after opening, and obtaining the polymer fiber, wherein the amount of paraffin oil sprayed is 0.1% to 1% of the mass of the polymer fiber.

3. The composite fiber according to claim 1, characterized in that, The polymer fiber is a monofilamentous polymer fiber with a diameter of 10~30μm and a length of 3~12mm; the wood fiber is a flocculent wood fiber with a length of 2~3mm.

4. A composite fiber according to claim 1, characterized in that, The polymethyl methacrylate is composed of polymethyl methacrylate Altuglas BS 203 and polymethyl methacrylate Altuglas BS 215 in a mass ratio of 2:2~3.

5. A process for preparing a composite fiber, used to prepare the composite fiber according to any one of claims 1 to 4, characterized in that, Includes the following steps: S1. Modified basalt fiber is obtained by spraying a modifier onto the surface of the basalt fiber. After the modified basalt fiber is desiccated, granulated, slag removed by sieving, shortened and opened, paraffin oil is sprayed onto the surface of the modified basalt fiber to prepare modified flocculent basalt fiber. S2. Spray paraffin oil onto the surface of the wood fiber, add the modified flocculent basalt fiber and the polymer fiber, mix evenly to obtain the material; S3. After the material is combed twice, it is then air-separated to remove slag and compressed and packaged to obtain the composite fiber.

6. The preparation process of a composite fiber according to claim 5, characterized in that, The two combing processes have different combing speeds. In the first combing process, the receiving roller of the first combing machine rotates at 30~60 rpm, the combing roller rotates at 800~1200 rpm, and the distance between the two rollers is 3mm~7mm. In the second combing process, the receiving roller of the second combing machine rotates at 30~60 rpm, the combing roller rotates at 1200~1500 rpm, and the distance between the two rollers is 1mm~5mm.

Citation Information

Patent Citations

  • Composite fiber for crack-resistant reinforced asphalt concrete, asphalt concrete and preparation method of composite fiber

    CN119349916A

  • Complex fibers for asphalt concrete

    CN103803829A